A Case Study on Reading Achievement of Eighth- Grade Students at MTs in Badegan Ponorogo - Mu’awanah, Roudlotul; Harida, Ratri; Putra, Tomy Kartika (STKIP PGRI Ponorogo Press, 2025)
This study investigates the difficulties of eighth-graders in comprehending English reading texts and what leads to those difficulties. Employing the case study strategy, this study recruited 52 students at Badegan’s junior high school, Ponorogo as the subjects. Data were collected using questionnaires and interviews and analyzed quantitatively with the Likert scale and qualitatively with thematic analysis. Findings revealed that the main challenges students had were understanding the overall gist of texts (M = 3.06), limited mastery over vocabulary (M = 2.92), and difficulty following English grammar and sentence structure (M = 2.73). The other areas included main and supporting points, understanding idioms, and grasping word roles. Apart from language issues, there were also some non-linguistic variables found to affect comprehension, such as inadequate reading time (M = 2.98), insufficiency of practice (M = 2.83), and lack of strategies for reading provided by teachers (M = 2.69). All these results indicate that internal and external factors interact to hinder reading comprehension among the students.